CIGARETTE SMOKE EXPOSURE AND ACUTE RESPIRATORY INFECTIONS AS RISK FACTORS OF STUNTING IN CHILDREN UNDER FIVE YEARS - Bagas Abdillah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Introduction: Previous studies suggest that cigarette smoke exposure and acute respiratory infections (ARI) are considered contributing factors. We analyzed the risk of cigarette smoke exposure and ARI incidence in association with stunting in children under 5 years of age in an Indonesian rural setting where smoking and ARI prevalences are high. Methods: This is an observational analytical study with a case–control design. Secondary data on stunting were obtained from height measurements in March 2020, whereas data on cigarette smoke exposure and the incidence of ARI were the primary data obtained from interviews. Results: After adjusting for other variables in the multivariable analysis, high exposure of cigarette smoke exposure (OR = 9.85, 95% C1 = 2.23 – 43.48) and frequent ARI incidence (OR = 7.32. 95% CI = 1.42 – 37.68) still demonstrated a significant association with stunting in children under 5 years of age; history of low birth weight and family income were among the associated covariate variables. Conclusion: These findings are consistent with those of previous studies. Cigarette smoke exposure and acute respiratory infections are associated with stunting in children under 5 years of age. Further robust studies are essential to confirm these findings.